Kepuasan wisatawan terhadap objek wisata pemancingan di Desa Konda Satu Kecamatan Konda Kabupaten Konawe Selatan - Halik, Aridho Rahmat Akbar; Rosmawati; Sadarun, Baru; Budiyanto; Mansyur, Akhmad; Risfandi (Jurnal Sosial Ekonomi Perikanan, 2022)
Satisfaction is the level of one's feelings after comparing the perceived performance (performance or results) with their expectations. While tourist satisfaction is a feeling of pleasure or satisfaction after visiting a tourist attraction. The purpose of this study was to determine tourist satisfaction with employee services and facilities for fishing tourism objects. This research was conducted on Urane Fishing in Konda Satu Village, Konda District, South Konawe Regency, from February to March 2021. The sample method used was accidental sampling with a sample of 30 tourists. Analysis of the data used is Importance Performance Analysis (IPA), as a result obtained that the rating of tourists is very satisfied with the service of employees with a score of 4.15. while the rating of tourists is very satisfied with the tourist attraction facilities with a score of 4.42.